(untitled) (Research, Society and Development, 2021)
Objective: To analyze maternal age, association with intercurrences during pregnancy and influence on the determination of childbirth. Method: Observational, retrospective, cross-sectional study with puerperae whose births occurred in 2016, in a hospital in the interior of São Paulo. Results: Of 1130 records analyzed, 22.2% presented <19 years and 10.3% ≥ 35 years. urinary tract infection occurred in 21.1% of the women, preterm labor (5.3%), premature placenta detachment (5.2%) and pregnancy-specific hypertensive disease (4.2%). diabetes and arterial hypertension were more frequent among women with ≥ 35 years of age, 57.9% of women had normal delivery and 42.1% had cesarean, a higher rate among women <19 years. Hypertension was associated with cesarean section in pregnant women ≥ 35 years old and pregnancy-specific hypertensive disease at normal delivery. Conclusions: Maternal age, pregnant women <19 years was associated with cesarean section and in pregnancies> 35 vaginal delivery was more frequent and regardless of age, the most frequent gestational complication was a urinary tract infection.